Stability of social support during school transitions: Associations with truancy and not completing upper secondary education in normative time. (December 2022) - Virtanen, Tuomo; Vasalampi, Kati; Lerkkanen, Marja-Kristiina; Pelkonen, Jenni; Poikkeus, Anna-Maija
Abstract: Not completing upper secondary education is often presignaled by truancy from school. Student-perceived social support from family, peers, and teachers can prevent truancy and the risk of not completing education. However, prior studies have not focused on the stability of social support across school transitions. This longitudinal study of 1901 Finnish students examined the extent to which social support was stable or specific to primary, lower secondary, and upper secondary schools. Moreover, we examined whether support was associated with not completing upper secondary education in normative time and whether truancy mediated the relationship between support and not completing education. The analyses showed that most variance in social support was context-specific; family and peer support was related to truancy and not completing education; and truancy acted as the mediator. The findings underscored the importance of stable social support over school transitions in reducing the likelihood of truancy and not completing education. Highlights: We examined stability of student-perceived support across two school transitions. Links between support, truancy, and not completing education were also explored. Most variance in student-perceived support was specific to school level. Family and peer support was related to truancy and not completing education. Teacher support predicted a lower likelihood of truancy.